The United States, UNCLOS, and the "Race to the Arctic" - Carmichael, Cade, 1987- (2018)
The Arctic is one of the most rapidly changing and fiercely debated regions in the era of climate change-related disputes and regulations. As a result of these changes and controversies, a “Race to the Arctic” has begun among a contingency of the world’s most powerful nations. The goal of this “race” is both to acquire Arctic resources and to make territorial claims in order to extend a given nation’s power. In many aspects, this “race” is as much legal as it is ideological or political. As such, a newfound legal regime is beginning to form around the inherent complexities of the Arctic. This regime is comparatively young and as such is multi-faceted in its approach to the “Race to the Arctic.” However, one of the most critical instruments of this burgeoning Arctic law regime is the United Nations Convention on the Law of the Sea (“UNCLOS”). While UNCLOS’s present formulation can be traced to 1982 and thus predates the “Race to the Arctic” in a contemporary sense, the Convention contains articles and legal bodies which are highly applicable to the Arctic. It is through this convention that many believe the future of the Arctic will be shaped. The glaring issue with this hypothesis is that the United States, an Arctic nation and one of the most militarily and economically powerful countries on Earth, has yet to ratify UNCLOS. This is a perplexing situation as the United States was not only involved in the formulation of UNCLOS, it would also stand to benefit in a large variety of ways by becoming a party to it. However, long-lasting notions of sovereignty and reliance on customary international law have stalled United States ratification and have subsequently hindered not only United States foreign policy efforts in the Arctic, but arguably the entirety of UNCLOS as a legal regime. This thesis seeks to explain why the United States has failed to ratify UNCLOS over the course of nearly thirty years, and further, to explain what it’s non-party status means for UNCLOS, it’s tribunals, and the future of the Arctic ...